Recycling Utilization of Copper Sulfide Mining Solid Waste - Huaqin HAN; Jinchun XUE; Ruoyan CAI; Zhuyu ZHAO; Li TAN (Kuangchan zonghe liyong)
Copper sulfide solid waste as a representative bulk solid waste, its resource utilization and disposal have always been a research hotspot in the field of mining and mining. In order to meet the demand of copper sulfide mine reclamation and ecological restoration for a large number of plant-derived substrates, remediating the bottom sludge of acidic wastewater by increasing fertilizer, thereby replacing the soil as a plant substrate for ecological restoration. Realized the resource utilization of acid wastewater solid waste from copper sulfide mine at the same time, based on the investigation of plant resources in the mining area, the feasibility of the method was verified by the bottom sediment pile soil test and the ground planting test, and the suitable plants for the ecological restoration of the bottom sediment were screened out. The results showed that the sediment with the addition of the conditioner had ideal vegetative characteristics, and the method of disposition was simple. In addition, zeamexicana, ryegrass, photiniafrase, ligustrumlucidum, false acacia and aspen were selected as suitable plants for the ecological restoration of sediment. The results of this study can provide reference to the same type of mining solid waste resource utilization.